Activity of Phage-Lactoferrin Mixture against Multi Drug Resistant Staphylococcus aureus Biofilms - Katarzyna Kosznik-Kwaśnicka; Natalia Kaźmierczak; Lidia Piechowicz (MDPI AG, 2022)
Biofilms are complex bacterial structures composed of bacterial cells embedded in extracellular polymeric substances (EPS) consisting of polysaccharides, proteins and lipids. As a result, biofilms are difficult to eradicate using both mechanical methods, i.e., scraping, and chemical methods such as disinfectants or antibiotics. Bacteriophages are shown to be able to act as anti-biofilm agents, with the ability to penetrate through the matrix and reach the bacterial cells. However, they also seem to have their limitations. After several hours of treatment with phages, the biofilm tends to grow back and phage-resistant bacteria emerge. Therefore, it is now recommended to use a mixture of phages and other antibacterial agents in order to increase treatment efficiency. In our work we have paired staphylococcal phages with lactoferrin, a protein with proven anti-biofilm proprieties. By analyzing the biofilm biomass and metabolic activity, we have observed that the addition of lactoferrin to phage lysate accelerated the anti-biofilm effect of phages and also prevented biofilm re-growth. Therefore, this combination might have a potential use in biofilm eradication procedures in medical settings.